How to choose the appropriate cannulation technique for vascular access in hemodialysis patients. Issue 3 (8th February 2023) - Sousa, Clemente Neves; Teles, Paulo; Ribeiro, Olga Maria Pimenta Lopes; Sousa, Rui; Lira, Marta Nunes; Delgado, Elisabete; Oliveira, Debora; Campos, Luís; Fernandes, Filipa; Moura, Sandra Cristina Mendo; Delgado, Millena Freire; Sá, Tiago Gomes; et al.
Abstract: The cannulation technique is important for the survival of the arteriovenous access. Choosing the appropriate technique is a complex decision. Such choice must be customized to patients, considering their characteristics, the type of arteriovenous access and the experience of the hemodialysis team. We describe seven items that can help nurses to identify the appropriate cannulation technique: type of arteriovenous access; drainage vein; hygienic self‐care profile; experience of the nursing staff in the cannulation technique and nurse‐to‐patient ratio; hemodialysis treatment method; patient's condition; and patient's decision. Such items can help nurses in decision‐making on the "ideal" cannulation technique for each patient.